Parenteral nutrition in critical illness: total, supplemental or never?. Issue 2 (10th March 2021) - Ridley, Emma J.
Abstract : Purpose of review: The current review summarizes recent evolutions in knowledge and discusses the concept of whom and when parenteral nutrition should be considered in critically ill patients as a total form of nutrition, in a supplemental form, or never. Recent findings: Recent developments in our understanding of the application of parenteral nutrition in critical care include the phases of illness, avoidance of overfeeding and the population in whom parenteral nutrition may be appropriate for. Importantly, one of the greatest lessons of recent times may be who not to provide parenteral nutrition to; however, a blanket approach of increased risk with parenteral nutrition is too simple for the modern context. Summary: When providing total or supplemental parenteral nutrition, avoidance of overfeeding with total calories and/or glucose alone is critical, as is consideration to the phase of illness the patient is in, the population in whom it is to be applied, premorbid nutrition status and the setting (including adequacy of line management and expertise in parenteral nutrition provision). The appropriateness of parenteral nutrition should be considered in those where death is imminent or who are well nourished, likely to commence oral and/or enteral nutrition imminently and have a short-stay in intensive care, or are in a high-risk setting.